Age-Related Water Use Pattern of the Introduced Species Atriplex canescens Was Influenced by Root Distribution in Desert - Hai Zhou; Xiangyan Feng; Zhibin He; Bing Liu; Fang Li; Heng Ren; Qiyue Yang; Jianjun Kang; Shuai Wang; Wenzhi Zhao (Ecosystem Health and Sustainability)
Atriplex canescens (Pursh) is extensively utilized for the phytoremediation of degraded lands in regions worldwide where water is the primary growth-limiting factor. However, little is known about the dynamics of root water uptake and age-related water sources for the shrubs, which restricts the efficacy of vegetation restoration. Here, we examined the distribution of roots and isotopic values of δ18O and δD in soil water at depths ranging from 0 to 300 cm, groundwater, precipitation, and shrub xylem at different stages of shrub maturity to determine water use patterns in shrub plantations. Our findings showed that the number of fine roots in the soil profile increased as the A. canescens shrub aged. At 2 and 5 years old, approximately 50% of the shrub roots were within the shallow soil layer (0 to 0.5 m soil depth), and they relied on shallow and mid-soil (0.5 to 1.5 m soil depth) water sources, recharged primarily by precipitation, to supply more than 60% of their water during the growing season. In contrast, 10-year-old A. canescens relied heavily on deep soil water and groundwater sources, despite the fact that less than 10% of their roots extended beyond 2 m soil depth. Thus, the shrub A. canescens became more suited to extremely dry conditions as it grew older because its roots allowed it to absorb deeper water from the soil rather than simply superficial water. It also implies that deep soil water and groundwater are crucial for vegetation restoration in desert regions.